The Dimensional Structure of the Schizotypal Personality Questionnaire Adapted for Children (SPQ-C-D): An Evaluation in the Dutch Population and a Comparison to Adult Populations. (5th March 2015) - van Rijn, Sophie; Kroonenberg, Pieter; Ziermans, Tim; Swaab, Hanna
Abstract : The increasing interest in dimensional approaches towards schizophrenia spectrum pathology calls for instruments that can be used to study developmental markers conveying risk for psychopathology prior to onset of the disorder. In this study we evaluated the Dutch child version (SPQ-C-D) of the Schizotypal Personality Questionnaire (SPQ) developed by Raine, in terms of reliability and factorial structure in comparison to SPQ data from two studies with adults. The 74-item SPQ-C-D was completed by 219 children and adolescents aged 9 to 18 years. Internal consistency was assessed and the factorial structure was analyzed using principal component analysis (PCA) and confirmatory factor analysis. Results showed that most of the subscales had high Cronbach's alphas, indicating good internal consistency. PCA resulted in three components, similar to the adult studies: Cognitive-Perceptual, Interpersonal, and Disorganization. The pattern of individual subscales loading on each of the components was identical to the original Raine study, except for one additional subscale loading on the Disorganization component. In addition, forcing Raine's factorial structure on our data with confirmatory factor analysis resulted in an overall adequate model fit. In conclusion, the SPQ-C-D appears to be a suitable dimensional measure of schizotypal traits in populations aged 9 to 18 years.